Instinctive versus reflective trust in the European Central Bank - Siria Angino; Stefania Secola (European Central Bank (ECB), 2022)
Political science research has established that trust in institutions, including central banks, is shaped by socio-economic and demographic factors, as well as by the assessment of institutional features and by slow-moving components such as culture. However, the role of cognitive processes has largely been neglected, especially in the analysis of central bank trust. In this paper we aim to address this gap focusing on the case of the European Central Bank (ECB).We introduce the concepts of "instinctive trust", which captures an on-the-spot judgement on the institution's trustworthiness, and of "reflective trust", which refers to a more pondered opinion on the matter. Using a survey experiment, we find that deeper consideration about the ECB promotes less trust in the institution compared to an on-the-spot judgement. This result is mainly driven by women, and in particular by those who say they possess a low understanding of the central bank's policies.
Keywords: C83; D83; E58; Z13; 330; Institutional trust; survey experiment; central bank